Application of time-resolved autofluorescence to label-free in vivo optical mapping of changes in tissue matrix and metabolism associated with myocardial infarction and heart failure - Lagarto,J; Dyer,BT; Talbot,C; Sikkel,MB; Peters,NS; French,PMW; Lyon,AR; Dunsby,C (Biomedical Optics Express, 2015)
We investigate the potential of an instrument combining timeresolvedspectrofluorometry and diffuse reflectance spectroscopy tomeasure structural and metabolic changes in cardiac tissue in vivo in a 16week post-myocardial infarction heart failure model in rats. In the scarregion, we observed changes in the fluorescence signal that can beexplained by increased collagen content, which is in good agreement withhistology. In areas remote from the scar tissue, we measured changes in thefluorescence signal (p < 0.001) that cannot be explained by differences incollagen content and we attribute this to altered metabolism within themyocardium. A linear discriminant analysis algorithm was applied to themeasurements to predict the tissue disease state. When we combine allmeasurements, our results reveal high diagnostic accuracy in the infarctedarea (100%) and border zone (94.44%) as well as in remote regions fromthe scar (> 77%). Overall, our results demonstrate the potential of ourinstrument to characterize structural and metabolic changes in a failing heartin vivo without using exogenous labels.